Perancangan Ulang Rem Tromol Pada Mobil Daihatsu Sirion Tahun 2020 - Doni Setyawan; Kardiman Kardiman; Iwan Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
Indonesia has a lot of people who use vehicles as a means of transportation for the community, especially motorbikes and cars. With the increase in the number of vehicles, it becomes very important when viewed from the safety and security point of view, one of the causes of road accidents is the brakes that do not function properly or are damaged. Therefore, in this study, we designed a drum brake on one of the 2020 Daihatsu Sirion cars to be safe while driving. Then the results of the analysis obtained a total vehicle loading force of 13,720 N and a frictional force of 37.92 N on the tires as a result of this, each front and rear wheel has a force of 115.21 N and 94.79 N. While the torque on the brakes is The resulting torque is 152.2 N. As a result of this torque, the reaction force on the brakes is 3.72 KN. While the safety factor generated from the analysis is 3.34, which means the number is above the standard machine element safety factor, namely 1, with a canvas life of 120 days.